รูปแบบความสัมพันธ์โครงสร้างเชิงสาเหตุของปัจจัยที่ส่งผลต่อกลยุทธ์การตลาด สำหรับธุรกิจแฟชั่นเครื่องนุ่งห่มไทยสู่ตลาดประชาคมเศรษฐกิจอาเซียน - กุลฐากรเสฏฐ์ ณัฏฐ์เอก (Journal of Business, Innovation and Sustainability (JBIS), 2015)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาระดับกลยุทธ์การตลาดสำหรับธุรกิจแฟชั่นเครื่องนุ่งห่มไทยสู่ตลาดประชาคมเศรษฐกิจอาเซียน และศึกษารูปแบบความสัมพันธ์โครงสร้างเชิงสาเหตุของปัจจัยด้านข้อมูลธุรกิจแฟชั่นเครื่องนุ่งห่มไทย และทุนปัญญาที่ส่งผลต่อกลยุทธ์การตลาดสำหรับธุรกิจแฟชั่นเครื่องนุ่งห่มไทยสู่ตลาดประชาคมเศรษฐกิจอาเซียน วิธีการวิจัยได้สุ่มตัวอย่างหลายขั้นตอนโดยการสุ่มตัวอย่างแบบชั้นภูมิใน 2 กลุ่มตามขนาดธุรกิจ และสุ่มตัวอย่างแบบโควค้า โดยมีขนาดกลุ่มตัวอย่างเท่ากับ 940 คน รูปแบบความสัมพันธ์โครงสร้างเชิงสาเหตุที่พัฒนาขึ้นมีความกลมกลืนกับข้อมูลเชิงประจักษ์ ตลอดจนมีความสามารถในการพยากรณ์ได้ระดับดีและเป็นที่ยอมรับคิดเป็นร้อยละ 61.2 ความสัมพันธ์เชิงสาเหตุพบว่า ปัจจัยด้านข้อมูลธุรกิจแฟชั่นเครื่องนุ่งห่มไทยได้แก่ ลักษณะของกิจการ ลักษณะความเป็นเจ้าของ ระยะเวลาดำเนินกิจการ ประเทศอาเซียนที่ทำการตลาด ประเภทผลิตภัณฑ์ที่ผลิตและ/หรือจำหน่าย ผลการดำเนินกิจการในปัจจุบันเมื่อเทียบกับปีที่ผ่านมา การทำการตลาดประชาคมเศรษฐกิจอาเซียนสำหรับกรณีการคอรัปชั่น และปัจจัยด้านทุนปัญญามีความสัมพันธ์เชิงสาเหตุต่อกลยุทธ์การตลาดสำหรับธุรกิจแฟชั่นเครื่องนุ่งห่มไทยสู่ตลาดประชาคมเศรษฐกิจอาเซียนอย่างมีนัยสำคัญทางสถิติ 0.05 The Structural Equation Model of Causal Factors Influencing Marketing Strategies For Fashion Business of Thai Garment towards the ASEAN Economic Community Market The objectives of this research were to study levels of strategies for the fashion business of Thai garment towards the ASEAN Economic Community market and to study the structural equation model of causal factors on the fashion business of Thai garment as well as the intellectual capital influencing the marketing strategies for the fashion business of Thai clothing towards the ASEAN Economic Community (AEC) market. The research method employed multi-stage sampling based on stratified random sampling in 2 groups according to the size of business and applied the quota of 940 sample size. The causal relationship of the structural equation model was created consistently with the empirical data and had the ability to predict at a good level and at the level of acceptance of 61.2 percent. According to the causal relationship, it was found that the factors on the fashion business of Thai garment comprised sizes, owners, business periods, markets in AEC member countries, kinds of products and, current outcomes as compared to those in the previous year. Meanwhile, marketing in AEC and intellectual capital had causal relationship with fashion business of Thai garment towards the AEC market at the statistically significant level of 0.05 DOI: http://dx.doi.org/10.14456/becj.2015.24